Pengaruh Konsentrasi Ekstrak Etanol Kunyit dan Daun Asam (Curcuma domestica Val.-Tamarindus indica L.) terhadap Karakteristik Krim - Simamora, Viva Yani Tika Rutmana; Mulyani, Sri; Harsojuwono, Bambang Admadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 3 (2020): SeptemberDO - 10.24843/JRMA.2020.v08.i03.p03, 2020)
This study aims to determine the effect of the concentration of turmeric and tamarind leaves ethanol extract (Curcuma domestica Val.-Tamarindus indica L.) on the characteristics of the cream and determine the concentration of turmeric and tamarind leaves ethanol extract which the best cream characteristics. The research used Complete Randomized Design. The treatment of the concentration of turmeric and tamarind leaves ethanol extract which consists of 6 levels, 0, 1, 2, 3, 4 and 5%. Each treatment was repeated 3 times, so 18 experimental units were obtained. Variables observed in turmeric and tamarind leaves cream are total phenol, anti-collagenase activity, pH, viscosity, spread-ability, adhesion, and separation ratio. The treatment of the concentration of turmeric and tamarind leaves ethanol extract affected the adhesion, separation ratio, viscosity, spread-ability and anti-collagenase of the cream, but did not affected the pH and total phenol cream. The treatment of turmeric and tamarind leaves ethanol extract 4 (four) percent was the best treatment to produced cream with the following criteria: adhesion = 70.29 seconds, spread-ability = 5.48 cm, separation ratio = 0.94, pH = 5.85, viscosity = 6.433 cp, total phenol = 1.60 mg GAE/mL and the best anti-collagenase (IC 50 ) = 0.89 µg/ml. Keywords: turmeric , tamarind leaves, anti-collagenase activity, characteristics of the cream.